On occupational safety in Ukraine in the context of social risks of preserving human capital - Olga Hrynkevych; Petro Ostroverkh; Vasyl Hrynkevych (Економічний форум)
The study is dedicated to the problem of human capital loss due to harmful working conditions, violations of occupational safety legislation, and other social risks in the labor sphere. The article aims to determine the trends and features of the dynamics of the working conditions indicators in Ukraine in the context of the Sustainable Development Goals, decent work criteria, and risks of preserving human capital associated with Russian military aggression. The authors use desk research methods, statistical methods to analyze the dynamics and structure of indicators of official statistics, and administrative data on occupational diseases, injuries, and industrial accidents, considering the SDG monitoring program in Ukraine. The study results showed that in Ukraine in 2016-2022, the level of social risks in the field of occupational safety remained high. The main contributors include a significant amount of employment in the informal sector of the economy, the limited ability of inspectors of the State Labor Service of Ukraine to prevent violations in the field of labor safety and occupational health, the low level of legal culture and awareness of employees with harmful working conditions, insufficient level of employer social and economic motivation to provide decent health and safety performance Due to Russian military aggression, the crisis factors of occupational safety are expanding significantly. Systemic solutions in state regulation of employee safety and health are paramount to prevent and reduce their negative impact. Such decisions should take into account the provisions of the Agreement on the Ukraine-EU Association, the International Labor Organization, ratified by Ukraine, the need to develop and implement new standards for professional risks management and their integration into the general management system of the enterprise, increasing the effectiveness of state control over compliance with labor legislation, and economic incentives for employers to provide decent working conditions following the Sustainable Development Goals